Improving subscriber viewing experience via the integration of contents from multiple broadband service providers based on open access policy - Ismail, Mohd Zahid (2011)
Present high-speed broadband services in Malaysia has yet to improve the Viewing Experience quality of the average subscribers as current single service provider channel packaging cannot address the specific needs and goals of diversified subscribers. Furthermore there is no common platform to integrate contents from licensed service providers and independent content providers alike. The objective of this research is to determine the content integration strategy that can address multiple-sourced content delivery that can improve the level of Quality of Experience of the subscribers. This paper will examine the Open Access-based content management and integration strategy which will allow subscribers more choices of subscription and more categories of services to which gives the subscribers more choices as well as managing their subscription preferences from their own household. In the future this study will be used as input by high speed broadband service providers in analyzing methods to increase their service delivery revenue by increasing the level of subscriber satisfaction.